Florística vascular não arbórea em uma Reserva Particular do Patrimônio Natural (RPPN) na Floresta Atlântica de São Paulo, Brasil - Saka, Mariana Naomi [UNESP]; Lombardi, Julio Antonio [UNESP] (FapUNIFESP (SciELO), 2016)
The private owned conservation area of RPPN Paiol Maria includes 76 ha of montane forest located at the municipality of São Lourenço da Serra, São Paulo State, belongs to the biodiversity corridor of the Serra do Mar, and is located at the northern part of Ribeira valley. This study was carried out during the period of June 2010 to September 2011 and our aim was to elaborate a checklist of the non-arboreal species occurring in the RPPN. A total of 330 species, distributed in 84 families and 223 genera were collected. Four species recorded for this work appears in the red list for the state of São Paulo. A similarity analysis between the epiphytes found in the RPPN and other four areas of montane forest reassert the important role of secondary forest fragments to the knowledge and conservation of the Atlantic Forest biodiversity.
Non-arboreal vascular flora of an Atlantic Forest area in Sao Paulo, Brazil
Keywords: Atlantic Forest; Epiphytes; Montane forest; Secondary forest